1985
DOI: 10.1021/jm00146a029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antineoplastic evaluations of 5,8-bis[(aminoalkyl)amino]-1-azaanthracene-9,10-diones

Abstract: Several 5,8-bis[(aminoalkyl)amino]-1-azaanthracene-9,10-diones have been synthesized and evaluated for antitumor activity against L1210 leukemia both in vitro and in vivo. Comparisons are made to the corresponding carbocyclic analogues. One of the aza analogues showed modest in vivo activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…PIX, an analogue of MX, was designed to reduce cardiotoxicity by removing the OH groups that are likely responsible for free-radical production and cardiotoxicity, while retaining and enhancing the molecules that provide the cytotoxicity action [54]. The absence of severe cardiotoxicity and a better efficacy of PIX compared with other anthracyclines have been confirmed in patients with aggressive or indolent non-Hodgkin's lymphomas.…”
Section: Pixantronementioning
confidence: 99%
“…PIX, an analogue of MX, was designed to reduce cardiotoxicity by removing the OH groups that are likely responsible for free-radical production and cardiotoxicity, while retaining and enhancing the molecules that provide the cytotoxicity action [54]. The absence of severe cardiotoxicity and a better efficacy of PIX compared with other anthracyclines have been confirmed in patients with aggressive or indolent non-Hodgkin's lymphomas.…”
Section: Pixantronementioning
confidence: 99%
“…Aza- and diaza-anthraquinones such as those depicted in Figure 1 , represent an important class of antitumor agents that exhibit promising in vitro and in vivo activity on tumor cell lines [ 9 , 10 , 11 , 12 , 13 ]. The antitumor activity of these agents seem to be mediated by DNA intercalation and redox cycling processes that are improved by the basic and electron-withdrawing properties of the N -heterocyclic ring [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the drawback of cardiotoxic effects, a pyrazole ring is fused to the anthraquinone moiety, giving a tetracyclic system in an attempt to reduce toxicity or modify the activity of the lead compound, and may alter the metabolism of the lead (Krapcho et al 1985;Krapcho et al 1994;Gandolfi et al 1995). Losoxantrone , is an anthrapyrazole derivative and found that sharing similar pharmacokinetics (Graham et al 1992), behaving almost similarly in the in vitro National Cancer Institute (NCI) cell screen and exhibiting the same anticancer spectrum of activity as MX with reduced cardiotoxicity (Leteurtre et al 1994).…”
Section: Introductionmentioning
confidence: 99%